Effects of Raloxifene on the Proliferation and Apoptosis of Human Aortic Valve Interstitial Cells. (23rd November 2016) - Fu, Zhimin; Luo, Bin; Li, Mingpeng; Peng, Bin; Wang, Zheng
Abstract : We aimed to explore the effects of raloxifene (RAL) on the proliferation and apoptosis of human aortic valve interstitial cells (AVICs). Different concentrations of RAL were used to act on AVICs. MTS kit is used to test the effects of different concentrations of RAL on the proliferation of AVICs. Cell cycle and apoptosis test used flow cytometry after seven-day treatment. The relative expression levels of caspase-3 and caspase-8 are tested with RT-qPCR and Western blot. The results of MTS testing revealed that the absorbance value (OD value) of the cells in the concentration groups of 10 and 100 nmol/L RAL at a wavelength of 490 nm at five, seven, and nine days significantly decreased compared with that in the control group. Meanwhile, the results of flow cytometry of the cells collected after seven days showed that the ratio of the S stage and the cell apoptosis rate of AVICs can be significantly reduced by RAL in the concentration groups of 10 and 100 nmol/L. The mRNA and protein expressions of caspase-3 and caspase-8 were significantly decreased compared with those in the control group. This study laid the foundation for further treatment of aortic valve disease by using RAL.